The Relations of Words in Structure Section by Easa Bin Ibrahim Al-Rabee (D.480 A.H) on his Book Nidham Al-Ghareeb - draym (Journal of College of Education, 2023)
It is no secret to the linguistic specialist that the semantic fields are related to the dictionaries of meanings that arrange the words according to the topics. In order to apply the associative relations to them, I chose the book (Nidham Al-Ghareeb) by Issa bin Ibrahim Al-Rab’i, a prominent scholar of Linguistics in Yemen. The researcher applied the idea to Bab Al-Bunyan (structure field) with him. The research comes under the title: The Relations of Words in the Field of Structures by Issa bin Ibrahim al-Rab’i (480 AH) in his book Nizam al-Gharib. The field of structure was preceded by the preface and followed by the conclusion. The number of analyzed words reached eleven. The analysis aims at clarifying the meaning of each word, then reveal the relationship between the word and the semantic field. The research showed the ability of linguists, including al-Rubai, to tabulate and classify their linguistic stock, their knowledge of semantic fields and the mobilization of words that have a specific meaning. This means that they were first in semantic classifications. Mostly, Al-Rab’I states that word and provide the meaning, supported with Quranic text , or poem. Although there were a word with no meaning, the glossary was a good supportive to detect the meaning. So the study spot the light on agreement and disagreement in defining the word for linguistics. If the word mentioned in Quranic text , then we return to exegesis of Quran. We noted in Al-Rab’I mention of synonym.. and detect the relation between the structure section and words inside the section which are : relation between incomplete synonym and relation of part to all